Doric Capitals in Pessinus: A Brief Overview of Pessinus Architectural Activities - Adem Yurtsever (Anadolu Araştırmaları)
The city of Pessinus is located within the boundaries of Ballıhisar Village, approximately 16 km south of Sivrihisar district in Eskişehir, Turkey. The area where the city is situated was first known as Phrygia and then as Galatia in ancient times. A significant portion of the ancient city currently remains buried beneath the village settlement. The conducted excavations and research have demonstrated the city to have been an important cult center during Hellenistic and Roman times. Pessinus has a rich cultural heritage, and impressive examples of architectural layouts and designs can evidently be found within its ancient ruins. One of the notable surviving examples of ancient architecture in the city is the Doric capitals identified at various points. This study provides a detailed analysis of the material, design, and stylistic features of the Doric capitals identified in Pessinus. Furthermore, it examines the typological variety, details, and regional variations of these capitals, along with their contributions to the overall architectural design.